Prevalência e determinantes de oclusopatias nas dentições decídua, mista e permanente na cidade do Natal/RN - Lima, Rejane Bezerra de (2006)
This work is intended to bring a contribuition to the verification of the prevalance of malocclusion in the deciduous, permanent and mixed dentition in the student population in the city of Natal, Brazil. In this purpose, a sectional study of infantiles aging 5, 8 and 12 years old was carried out. The average prevalance of malocclusions in the group as a whole was 76,5%. Considering the different dentitions separately, the study showed malocclusion prevalence as follows: Deciduous Dentition 75,5%; Mixed Dentition 84% and Permanent Dentition 70,5%. The most common malocclusion cases found in the deciduous dentition were openbite (20.6%); overbite (16.6%) and maxillary overjet (14,7). Mixed Dentition: the most commonly found occlusional malfunctions in this dentitional phase were maxillary overjet (33,8%); crowding (28,3%), and mandillary discrepancy (19,9%). In the univaried analysis, he application of the Chi square test of independence, (significance 5%), has indicated a meaningful association of the variables social class (p=0,019), primata space (p = 0,036), habits (p= 0,002) and time-and-habit (P=0,03). The same test on the permanent dentition group revealed a significant association for the independent variables, as follows: Social class (p=O,OOO), School (p=O,OOI), Income (p=O,OOO), housing standard (p=0,001), facial pattem (p=0,004), caries record (p=0,031). No significant association was found in the mixed dentition. The Logistic Regression analysis on the deciduous dentition has shown that income, ethnicity, habit and canine relationship constitute factors of risk regardless of the other variables. As for the permanent dentition, only Facial Pattem was pointed as a factor of risk for the formation of malocclusion